Copyright act,1957 along with the copyright rules,1958 together with international copyright order,1999 with short notes (New Delhi, 2002)
In ancient days creative persons like artists, musicians and writers made, composed or wrote their works for fame and recognition rather than to earn a living, thus, the question of copyright never arose.
Keywords: Copyright-India